ADP-Ribose Transfer Reactions 1989
DOI: 10.1007/978-1-4615-8507-7_39
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-Ribose) May Signal Changing Metabolic Conditions to the Chromatin of Mammalian Cells

Abstract: In mammalian cells, NADI serves a dual role as a respiratory coenzyme and as a substrate for the posttranslational poly(ADP-ribose) modification of chromatin proteins, catalyzed by the nuclear enzyme poly(ADP-ribose) polymerase EC 2.4.2.30]. Biological evidence strongly suggests that poly(ADP-ribosyl)ation modulates chromatin functions, although the precise molecular mechanisms involved have not yet been elucidated. Here we describe conditions for the rapid uptake of exogenously supplied NADI by living hepato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…HLX1 (homeo box 1) is expressed in hematopoietic progenitors and activated lymphocytes and may regulate development of CD4ϩ T cells (62). ADPRT (ADP-ribosyltransferase) is induced by DNA damage and plays a role in cellular repair (63). The report that SLE patients and their family members had decreased poly(ADPribose) metabolism makes ADPRT a possible candidate (64).…”
Section: Discussionmentioning
confidence: 99%
“…HLX1 (homeo box 1) is expressed in hematopoietic progenitors and activated lymphocytes and may regulate development of CD4ϩ T cells (62). ADPRT (ADP-ribosyltransferase) is induced by DNA damage and plays a role in cellular repair (63). The report that SLE patients and their family members had decreased poly(ADPribose) metabolism makes ADPRT a possible candidate (64).…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, the level of chromatin-bound ADP-ribose polymers depends on the availability of NAD + (Loetscher et aL, 1987). Likewise, it has been shown that lactate affects ADP-ribose polymer levels in cultured fibroblasts by decreasing the NAD+/NADH ratios in these cells (Hussain et al, 1989).…”
Section: Discussionmentioning
confidence: 97%
“…DNA damage drastically stimulates utilization of NAD § for the poly ADPribosylation reaction, catalyzed by the nuclear enzyme poly(ADP-ribose) polymerase [EC 2.4.2.30], and this may cause a substantial depletion of cellular NAD § pools (for review see Althaus and Richter, 1987). On the other hand, the level of proteinbound poly(ADP-ribose) in chromatin depends on the availability of NAD § (Loetscher et al, 1987). At present, the biological significance of this functional relationship is not well understood.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, the cells treated with 3‐AP could maintain highly differentiated functions. It has been reported that intracellular NAD + accelerates the activity of PARP and that, by contrast, NAD + depletion can subsequently inhibit the enzymatic activity 41 . Although nicotinamide is a strong inhibitor of PARP, retained NAD + may stimulate the enzymatic activity and partially suppress the expression related to hepatic differentiation.…”
Section: Discussionmentioning
confidence: 99%